The Potency of Kaffir Lime Leaf (Citrus Hystrix) Ethanol Extract Against Lead Acetate Toxicity on Spermatozoa Quality of Mice (Mus musculus) - Azarine Ariqoh Arysanti Bahyshidqi; Safira Nur Izzah; Sofia Zahra Kamila; Reny I’tishom (Institute of Medico-legal Publications Pvt Ltd, 2021)
Lead is a heavy metal which can affect male reproductive system. The accumulation of lead in the bodybecomes a precursor to the formation of ROS, which is able to damage spermatozoa. The toxicity of leadcan be prevented by antioxidants. Kaffir lime leaves (Citrus hystrix) with their flavonoid content have thepotential to be the source of antioxidants. The purpose of this study is to analyze the antioxidant effect ofkaffir lime leaves on the quality of spermatozoa of the mice that have been exposed to lead acetate. Methods:The literature study was conducted using narrative review technique by collecting related articles usingspecified keywords. Result: It is found that kaffir lime leaves contain hesperetin, which is the dominantflavonoid in Citrus group. The antioxidant activity of kaffir lime leaf is able to neutralize lead-induced ROS,as well as to stimulate the formation of enzymatic antioxidants. Conclusions: Ethanol extract of kaffir limeleaves can improve the quality of spermatozoa of the mice that have been exposed to lead acetate.